Rapid review: use of community-wide surgical masks and acute respiratory infections - Dalia Stern; Nancy López-Olmedo; Carolina Pérez-Ferrer; Romina González-Morales; Francisco Canto-Osorio; Tonatiuh Barrientos-Gutiérrez (Instituto Nacional de Salud Pública, 2020)
Objective: To assess the effectiveness of using surgical masks in community settings to reduce the probability of infection by SARS-CoV-2 or other acute viral respiratory infection, compared to not using surgical masks.   Material and methods: We followed the Cochrane rapid review methodology. The search strategy encompasses one academic database and pre-prints until April 1, 2020. Titles and abstracts were reviewed by one investigator. The full text review was divided among three researchers. The results were synthesized in a narrative way.   Results: 713 manuscripts were identified, of which 21 met the inclusion criteria. Of six systematic reviews, four found no reduction in the probability of transmission. Experimental home studies found no differences in the probability of contagion associated with the use of mouth masks. Three modeling studies estimated reductions of 20% in the incidence of respiratory disease, assuming that 10 to 50% of the population has correct use of mouth masks.   Conclusions: We did not find sufficient scientific evidence to support the general use of surgical masks to reduce the number of viral respiratory infection.